Correlation Between Different Sagittal Parameters in Patients With Degenerative Kyphosis - Liang, Yan; Xu, Shuai; Guo, Chen; Mao, Keya; Liu, Haiying (Frontiers in Molecular Neuroscience, 2022)
Objective To explore the relationship between different sagittal parameters and identify the fitting formula of spino-pelvic parameters in patients with degenerative kyphosis (DK). Summary of Background Sagittal balance is increasingly recognized as a predictor of clinical outcomes in patients with DK. While the relationship between different sagittal parameters in patients with DK remains unidentified. Methods A retrospective study with 279 participants was conducted. There were 168 DK patients which divided into sagittal balance group (SB:52 cases) and sagittal imbalance (SIB:116 cases). Radiographic measurements included thoracolumbar kyphosis (TLK), lumbar lordosis (LL)，thoracic kyphosis(TK), pelvic incidence(PI) and pelvic tilt(PT). The correlations were analyzed between different sagittal parameters. Results There were significances between SB and SIB group in terms of TLK, LL, PI-LL, PT, SVA, SS and TK. For the patients with DK, the LL was correlated with PT and TK. The linear regression was LL=22.76-0.28×PT+0.62×TK. In SB group, TK was the influencing factor for LL and the linear regression analysis showed that LL=33.57+0.33×TK. While in SIB group, PT and TK were in synergistic effect with PI-LL, the linear regression analysis showed that LL=22.76-0.28×PT+0.62×TK. Conclusions From the present study, we can see that the LL has significant correlation with PT and TK in patients with DK. While in SB, the LL was only correlated with TK. Therefore, the correction of LL in different group should be calculated to avoid the incidence of proximal junction kyphosis (PJK).